2020
DOI: 10.1038/s41419-020-02758-6
|View full text |Cite
|
Sign up to set email alerts
|

Inactivating p53 is essential for nerve growth factor receptor to promote melanoma-initiating cell-stemmed tumorigenesis

Abstract: Nerve growth factor receptor (NGFR, CD271, or p75NTR) is highly expressed in melanoma-initiating cells (MICs) and is critical for their proliferation and tumorigenesis, and yet the underlying mechanism(s) remain incompletely understood. We previously showed that NGFR inhibits p53 activity in a negative feedback manner in various cancer cells. Here we report that this feedback inhibition of p53 by NGFR plays an essential role in maintaining the sphere formation (stem-like phenotype) and proliferation of MICs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…These receptors are also expressed on nerves, and p75 neurotrophin receptor has recently been reported to act as a chemoattractant for cancer cells (54). Indeed, cancer-derived NGF drives neurite growth and cancer proliferation and migration and is correlated with nervecancer crosstalk (1,(55)(56)(57)(58)(59)(60)(61)(62)(63)(64). One notable study demonstrated an association between expanded enteric nerves and increased NGF expression in gastric cancer and the NGF/Trk signaling regulation of Dclk1+ tuft-cell coordinated crosstalk between nerves and gastric cancer (64,65).…”
Section: Neurogenic Factors Promote Axonogenesis In Cancer Progressionmentioning
confidence: 99%
“…These receptors are also expressed on nerves, and p75 neurotrophin receptor has recently been reported to act as a chemoattractant for cancer cells (54). Indeed, cancer-derived NGF drives neurite growth and cancer proliferation and migration and is correlated with nervecancer crosstalk (1,(55)(56)(57)(58)(59)(60)(61)(62)(63)(64). One notable study demonstrated an association between expanded enteric nerves and increased NGF expression in gastric cancer and the NGF/Trk signaling regulation of Dclk1+ tuft-cell coordinated crosstalk between nerves and gastric cancer (64,65).…”
Section: Neurogenic Factors Promote Axonogenesis In Cancer Progressionmentioning
confidence: 99%
“…Cancer cells also utilize diverse oncogenic molecules to modulate the MDM2-p53 axis. For instance, NGFR and PHLDB3 that are highly expressed in multiple human cancers were found to undermine the stability and transcriptional activity of p53 by directly interacting with both MDM2 and p53 (14)(15)(16). In our recent attempt to uncover regulators of the MDM2-p53 circuit in colorectal cancer as further described below, we identified a long noncoding RNA (lncRNA) as a player crucial for cancer development and progression.…”
mentioning
confidence: 99%
“…Furthermore, nuclear translocation of p75 NTR ‐ICD helps modulate transcriptional events [23–25]. In addition, studies showed that the N terminus of p75 NTR can inactivate p53 by direct binding with its central DNA binding domain [26,27]. However, the knowledge of how p75 NTR proteolytic fragments play their roles in tumorigenesis is still largely unknown.…”
mentioning
confidence: 99%